BOOK AND FINANCIAL PERFORMANCE OF SMALL-SCALE ENTERPRISES IN BUGUJJU TRADING CENTRE MUKONO DISTRICT - MANDRE ISAAC (UGANDA CHRISTIAN UNIVERSITY, 2025)
The research report recognized the relationship between book keeping and financial performance of small-scale enterprises in Bugujju Trading Centre. To analyze the relationship between book keeping and financial performance and it also comprised of the credential information for the Research report and be composed of the statement of the problem, the study objectives, significance and research questions and relating the variables to come with book keeping as the independent and financial performance being the dependent the literature review and study on book keeping and financial performance of small-scale enterprises, overview of the challenges associated with book keeping and the types of books kept by the small-scale enterprises and analyze and evaluated what different scholars and researchers validate these variables. the research methodology which was also called the research design that was a cross-section research design, the research population was 50 and the sample size (n) was 44, interviews and questionnaires were the method I employed to collect data from the field which was composed of different nature of small-scale enterprises in Bugujju Trading Centre quality of data that was to say validity and reliability, various methods of data presentation the specific objectives of the study. The findings showed that proper book keeping can results into proper decision making in short- investments, and expansion of businesses can be archived by efficient and effective book from the field are analyzed and describe in this was section of the research study. The data offered in table format enabled easy interpretation of business responds about the types of books they kept, the monthly average income and expenses of the enterprises, the conclusion, recommendations of the research study being undertaken, where by the small-scale business owners and employees recommends that if there was any opportunity that will be availed to educate and trained them about book keeping practice they willing and more interested to be part of the exercise to effectively improve on their basic book keeping skills and knowledge that enhance their enterprises financial health.
UNDER GRADUATE